Institutional quality as the driver of fiscal decentralization in developing countries - Kumba Digdowiseiso (Cogent Economics & Finance, 2023)
In this essay, I argue that the various institutional settings of fiscal decentralization observed in developing countries are contingent on institutional quality. Other incentives may exist for policymakers to change the degrees of fiscal power. My research is based on a five-year average of data from 34 developing countries between 1990 and 2014.I employ the Generalized Method of Moments (GMM) to address the issue of endogeneity, which is a common issue in fiscal decentralization studies. The findings show a strong nonlinear relationship between institutional quality and fiscal decentralization metrics. In this context, since democracy (polity), participatory democracy, bureaucratic quality, law and order, and fiscal decentralization are all emerging from low levels of development, an increase in the magnitude of these institutional quality variables will further reduce fiscal autonomy.
Keywords: E62; H10; H70; R50; 330; Developing Countries; Fiscal Decentralization; Institutional Quality; Subnational Government Analysis